LITERATURE REVIEW : Pengaruh Aquatic Plyometric Training Terhadap Daya Tahan Otot Pada Pemain Basket - Agnia Mulyanisa (2020)
Basketball players to achieve maximum results in a match requires optimal physical fitness. Aims: The writing of this literature study aims to review the literature, journal, articles or the results of previous research with the discussion topic of the influence of aquatic plyometric training on muscular endurance in basketball players. Methods: Search for sources of literature, journals, articles, research results in various databases such as Google Scholar by using certain keywords. The results of the literature search found 4 journals and articles that met the source inclusion criteria. The methodological quality assessment of 4 journals and articles was assessed using the Scimago Journal & Country Rank (SJR) and The Level Of Internal Validity value with a minimum category B according to the Critical Appraisal of Studies. Analysis of 4 journals was carried out based on the suitability of the discussion topic, the research methods used, and the results of each article. Result: After analyzing the literature as many as 4 journals showed that aquatic plyometric training can increase someone's muscular endurance. Conclusion: Aquatic plyometric training can significantly increase the muscular endurance in basketball players.